2014
DOI: 10.1096/fj.14-258780
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nuclear receptor activity and epigenetic modulation associates with down‐regulation of hepatic drug‐metabolizing enzymes in chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) require many medications. CYP2C and CYP3A drug-metabolizing enzymes play a critical role in determining the pharmacokinetics of the majority of prescribed medications. These enzymes are transcriptionally regulated by the nuclear receptors pregnane X receptor (PXR) and hepatic nuclear factor 4␣ (HNF-4␣). Expression of CYP2C and CYP3A is decreased in CKD; however, the mechanisms by which this occurs is unknown. We induced CKD in rats by 5/6 nephrectomy and used chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Evaluation of plasma concentrations of indoxyl sulfate and parathyroid hormone may help to reveal the mechanism in patients with ESRD. Furthermore, a recent study suggests that CYP3A downregulation in renal failure may be mediated by decreased binding with the pregnane X receptor (PXR), a nuclear receptor that transcriptionally regulates CYP3A [33]. Recovery of PXR binding after kidney transplantation may also be involved in the increase in CYP3A activity after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of plasma concentrations of indoxyl sulfate and parathyroid hormone may help to reveal the mechanism in patients with ESRD. Furthermore, a recent study suggests that CYP3A downregulation in renal failure may be mediated by decreased binding with the pregnane X receptor (PXR), a nuclear receptor that transcriptionally regulates CYP3A [33]. Recovery of PXR binding after kidney transplantation may also be involved in the increase in CYP3A activity after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…51) It has also been reported that a decrease in the acetylation of histones near PXRE, which is located on the promoter of CYP3A2, leads to a decrease in the transcriptional activity of CYP3A2 in rats with chronic kidney disease. 52) In addition, it has been reported that there is an enhancement in histone acetyltransferase (HAT) activity at the time of neuropathic pain. 53) A possible mechanism underlying the increased expression of UGT2B can be proposed based on these reports.…”
Section: Fig 4 Amount Of Pxr Transported To the Nucleus Of Mice Witmentioning
confidence: 99%
“…PXR-mediated CYP3A4 induction was regulated by PRMT1, which methylated histone H4 at arginine-3 that is located within a PXR-responsive chromatin region in the CYP3A4 gene [94]. In a rat model of chronic kidney disease, reduced Cyp2C and Cyp3A expression, and associated reduction in PXR and HNF4- α binding to cognate sites in the Cyp2C11 and Cyp3A2 promoters, was accompanied by reduced histone H4 acetylation at the Cyp3A2 promoter regulatory region and reduced histone H3 acetylation at the PXR- and HNF4- α -bound regulatory loci of Cyp2C11 and Cyp3A2 promoters [95]. …”
Section: Genetics Epigenetics and Interindividual Differences In Dmentioning
confidence: 99%